Development of Android-based statistics learning simulation media to support student achievement - Mulyono, Budi; Kurniadi, Elika; Araiku, Jeri; Otniel, Otniel; Ratnanenci, Cici (Universitas Maritim Raja Ali Haji, 2023)
This study aims to (1) produce valid and practical android-based learning media and (2) determine the potential effects on learning outcomes and positive attitudes of students from the development of android-based learning media. The type of research used is research and development using a development model adapted from Plomp. The subjects tested in the research are students who have studied basic statistical material, especially on the size of data centering. Data collection techniques in this study consisted of questionnaires, tests, and interviews. The results of this study include (1) producing valid and practical android-based learning media and (2) having a potential effect on learning outcomes and students' positive attitudes.